Appendicorectal fistula with a novel solution: First case report and review of the literature. Issue 10 (21st August 2019) - McCrystal, Shaun; Kong, Joseph; Gourlas, Peter; Morris, Bradley; Lutton, Nicholas
Abstract: Appendicorectal fistula can be a cause of chronic abdominal pain, forming years after an occult episode of appendicitis. It can be diagnosed with Colonoscopy and Magnetic Resonance Imaging, and successfully treated surgically with laparoscopic appendicectomy and stapled segmental cuff resection of the rectum. Abstract : Appendicorectal fistula can be a cause of chronic abdominal pain, forming years after an occult episode of appendicitis. It can be diagnosed with Colonoscopy and Magnetic Resonance Imaging, and successfully treated surgically with laparoscopic appendicectomy and stapled segmental cuff resection of the rectum.